Co-culture with Tetragenococcus halophilus changed the response of Zygosaccharomyces rouxii to salt stress. (August 2020) - Yao, Shangjie; Zhou, Rongqing; Jin, Yao; Zhang, Liqiang; Huang, Jun; Wu, Chongde
Graphical abstract: Highlights: The interactions between yeast and LAB play roles in high salt fermentation. Co-culture benefited salt tolerance of Z. rouxii. Co-culture changed the response of Z. rouxii to salt stress on the physiological characterization. Abstract: Zygosaccharomyces rouxii and Tetragenococcus halophilus exhibit remarkable salt tolerance and play roles in high-salt fermented food production. This study investigated the effect of co-culture with T. halophilus on Z. rouxii based on analysis of the viability of Z. rouxii in high-salt environments, the plasma membrane integrity, Na +, K + -ATPase activity, amino acid content of Z. rouxii cell after salt stress and organic acids assay. The results showed both T. halophilus broth supernatant and intracellular component of T. halophilus increased the viability of Z. rouxii in the 12 % environment. Co-cultured Z. rouxii cells maintained better plasma membrane integrity and lowered Na +, K + -ATPase activity than single-cultured after salt stress. Co-cultured Z. rouxii cells exhibited higher contents of aspartic acid, threonine, serine, asparagine, glutamic acid, alanine, α-amino-n-butyric acid, methionine, homo-cystine, arginine and proline compared with single-cultured after salt stress. More contents of propionic acid, lactic acid and L-pyroglutamic acid and lower contents of L-malic acid and citric acid were detected in co-culture broth. This study shows preculture of T. halophilus and then co-culture with Z. rouxii enhanced the viability of Z. rouxii in high-salt environment. The results may contribute to further understand the interactions between Z. rouxii and T. halophilus in high-salt environments.